Paperless partogram: a simple clinical tool in effective labour management - Reshma, Shaik; Ambarkar, Sri Lakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Maternal mortality is unacceptably high, about 830 women die from pregnancy or child birth related complications around the world every-day. Prolonged and obstructed labour is one of the major causes of maternal and perinatal mortality and morbidity worldwide. In developing countries like India, around 5% of total maternal deaths are caused by prolonged and obstructed labour. The purpose of the present study is to evaluate the role of paperless partogram in management of labour, identification of abnormal labour and early intervention to prevent the maternal and perinatal morbidity. The objective of this study was to assess the role of paperless partogram in labour monitoring and decision-making in overburdened Indian labour room setup and to evaluate the outcome of the cases. Methods: A prospective study was conducted at a tertiary care hospital, Kurnool, Andhra Pradesh, between January 2020 to March 2020. A total of 300 pregnant mothers in established labour who fulfilled the inclusion criteria, were included in the study after taking informed consent. Results: In our study, of all the pregnant women 23 crossed the alert ETD but 16 had delivered vaginally and 2 by caesarean section before action ETD and 5 women crossed the action ETD. Among the 5 who crossed action ETD 3 delivered vaginally and 2 had cesarean section. Majority, of the women who crossed the alert and action ETDs were primigravidae. Conclusions: From our study, it is concluded that paperless partogram was effective and user friendly in management of labour and prevention of abnormal or prolonged labour.